2016
DOI: 10.1002/ece3.1894
|View full text |Cite
|
Sign up to set email alerts
|

Local parasite lineage sharing in temperate grassland birds provides clues about potential origins of Galapagos avian Plasmodium

Abstract: Oceanic archipelagos are vulnerable to natural introduction of parasites via migratory birds. Our aim was to characterize the geographic origins of two Plasmodium parasite lineages detected in the Galapagos Islands and in North American breeding bobolinks (Dolichonyx oryzivorus) that regularly stop in Galapagos during migration to their South American overwintering sites. We used samples from a grassland breeding bird assemblage in Nebraska, United States, and parasite DNA sequences from the Galapagos Islands,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 68 publications
0
15
0
Order By: Relevance
“…Each year, hundreds of species of birds leave their tropical and subtropical wintering areas for high‐latitude summer breeding grounds, returning to lower latitudes at the end of the breeding season (Alerstam et al ., ; Faaborg et al ., ). These species are exposed to different parasites in their boreal or temperate breeding areas and in their subtropical or tropical wintering areas, and they potentially could disperse parasites between these areas (Valkiūnas, ; Altizer et al ., ; Levin et al ., ; Smith & Ramey, ; Levin et al ., ), particularly because birds retain parasite infections through the annual cycle, and often for many years (e.g. Atkinson et al ., ).…”
Section: Introductionmentioning
confidence: 99%
“…Each year, hundreds of species of birds leave their tropical and subtropical wintering areas for high‐latitude summer breeding grounds, returning to lower latitudes at the end of the breeding season (Alerstam et al ., ; Faaborg et al ., ). These species are exposed to different parasites in their boreal or temperate breeding areas and in their subtropical or tropical wintering areas, and they potentially could disperse parasites between these areas (Valkiūnas, ; Altizer et al ., ; Levin et al ., ; Smith & Ramey, ; Levin et al ., ), particularly because birds retain parasite infections through the annual cycle, and often for many years (e.g. Atkinson et al ., ).…”
Section: Introductionmentioning
confidence: 99%
“…Migrating avian hosts have also been implicated in moving haemosporidian parasites from mainland areas to islands. For example, avian Plasmodium in the Galapagos Islands likely arrived via a migrating host, the Bobolink (Dolichonyx oryzivorus), which regularly stops over in the Galapagos archipelago during its migration (Levin et al, 2013(Levin et al, , 2016.…”
mentioning
confidence: 99%
“…DNA from the Bobolink blood sampled in Galapagos. Two of the sequences matched the Plasmodium cathemerium lineage SEIAUR01 (GenBank accession number: AY377128 , Loiseau et al, 2013 ), which is common in Bobolinks ( Levin et al, 2013 ) and corresponds to lineage M found in those captured in North America ( Levin et al, 2016 ). The other two sequences match Plasmodium sp.…”
Section: Resultsmentioning
confidence: 94%
“…In an earlier study, we found Plasmodium parasite lineages B and C, detected in 2 Galapagos passerine species, Small ground finches ( Geospiza fuliginosa ) and Yellow warblers ( Setophaga petechia ), in the blood of Bobolinks sampled on their North American breeding grounds ( Levin et al, 2013 ). We then characterized the geographic origins of these two lineages: Plasmodium lineage B was of South American origin and Plasmodium lineage C was of North American origin, potentially California ( Levin et al, 2016 ). Although these results offer a compelling explanation as to how parasites may have arrived on the Galapagos Islands, we sought more evidence for the role of the Bobolink in Plasmodium transmission to Galapagos resident birds by sampling Bobolinks for haemosporidian parasites in the Galapagos.…”
Section: Introductionmentioning
confidence: 99%